Peristiwa Isra' Mi'raj Nabi Muhammad SAW dan Pembelajarannya - Yuyun Yunita (MKKS SMA, MKKS SMP se-Kota Metro, Persatuan Sarjana Pendidikan Islam Wilayah Provinsi Lampung, dan CV.IQRO Penerbitan, 2021)
Israj Mi'raj is the event of the Prophet's journey from the Haram Mosque to the Aqsh Mosque, then the Prophet was brought up to Sidaratul vomitingara by the angel Gabriel by riding the Buraq. On this occasion Muslims were ordered to perform the five daily prayers. The person who first confirmed this incident was Abu Bakr for his bravery he earned the title as-Siddiq